Information Technology in problems of hydrodynamics - Буйвол, В. М.; Фоміна, Н. Б.; Наконечна, В. В. (Problems of Informatization and Management, 2010)
The results of studies from new package of applied mathematics to solve problems of hydrodynamic flows with free surfaces. Efficiency Package Maple in the problems of compression of spherical cavities in the liquid in the presence of fields hydrodynamically th pressure, gravity, surface tension and viscosity. The features of the process fu-skannya in these fields